Light and temperature as triggers for surface filamentous green algal blooms in shallow freshwater systems - Hannah R. Kemp; Alexandra Zieritz; Stephen J. Dugdale; Nico R. Helmsing; Suzanne Wiezer; Lisette N. de Senerpont Domis; Stephen C. Maberly; Martyn Kelly; Suzanne McGowan (Limnology and Oceanography, 2025)
Blooms of filamentous green algae (FGA) form dense mats at the surface of shallow freshwaters and have multiple negative impacts on aquatic ecosystem functions, services, and aesthetics. Although nutrient enrichment in freshwaters is a primary driver of excessive FGA growth, much less is known about other abiotic factors controlling bloom growth rate, extent, and timing. We performed a series of indoor mesocosm (Limnotron) experiments to investigate the effects of photosynthetically active radiation irradiance, photoperiod, and water temperature on the growth and surface bloom formation of FGA using underwater and surface photography. The results revealed that a minimum daily light integral of ~ 13.2 mol m −2 d −1 (a combination of photosynthetically active radiation irradiance measured at the water surface and daylength) was required for bloom formation and substantial FGA growth. Surface blooms did not occur at short daylengths (i.e., 8 h), whereas a long daylength (i.e., 16 h) allowed more time for photosynthetically derived gas bubbles to accrue in the FGA masses, making them rise to the water surface through buoyancy. We also found that temperatures between 16°C and 22°C were optimal for FGA to form surface blooms. As freshwater ecosystems are increasingly impacted by climate change, our study sheds new light on factors affecting the occurrence of surface blooms and helps identify when waterbodies may be at risk of FGA blooms in the future.